2003
DOI: 10.1088/0953-8984/15/38/010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation and simulation of hybrid organic/inorganic Schottky diodes

Abstract: We have investigated electronic transport in hybrid organic/inorganic Schottky diodes. In order to derive from basic principles the transport properties of the organic semiconductors, we have use a two-dimensional drift-diffusion simulator which properly accounts for transport in both organic and inorganic layers. We have calculated the I-V characteristics of Ag/PTCDA/GaAs Schottky diodes as a function of PTCDA thickness and compared the results with experimental in situ measurements. The interplay between bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…The case may be ascribed to an organic interlayer modifying the effective barrier height by influencing the space charge region of the inorganic substrate [23,54]. Thereby, it is known that the organic film forms a physical barrier between the metal and the Si substrate, preventing the metal from directly contacting the Si surface [17,18,[21][22][23][24][25][26]54]. The methyl violet organic layer appears to cause a significant modification of interface states even though the organic/inorganic interface becomes abrupt and unreactive [17,18,[21][22][23][24][25][26]54].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The case may be ascribed to an organic interlayer modifying the effective barrier height by influencing the space charge region of the inorganic substrate [23,54]. Thereby, it is known that the organic film forms a physical barrier between the metal and the Si substrate, preventing the metal from directly contacting the Si surface [17,18,[21][22][23][24][25][26]54]. The methyl violet organic layer appears to cause a significant modification of interface states even though the organic/inorganic interface becomes abrupt and unreactive [17,18,[21][22][23][24][25][26]54].…”
Section: Resultsmentioning
confidence: 99%
“…Namely, many devices using the polymeric [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and nonpolymeric organic materials [17][18][19][20][21][22][23][24][25][26][27][28][29] have been fabricated including light emitting diodes and Schottky (Metal/Semiconductor = MS) type devices like an inorganic semiconductor/ organic semiconductor material or a metal/organic semiconductor material, and their electrical and photoelectrical properties have been investigated for more than three decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA organic interlayer appears to cause a significant modification of interface states even though the organic-inorganic interface becomes abrupt and unreactive [14,47]. Thus, the change in barrier height can qualitatively be explained by an interface dipole induced by the organic layer passivation [12,15]. Kampen et al [12] have observed by photoemission spectroscopy investigations that the sulphur passivation reduces the surface band bending on n-type doped GaAs, whereas the band bending on the surfaces of p-type doped GaAs increases.…”
Section: Electrical Measurementsmentioning
confidence: 99%
“…For example, many devices using polymeric [1][2][3][4][5][6][7] and nonpolymeric organic materials [8][9][10][11][12][13][14][15], including light emitting diodes and devices, such as an inorganic/organic and a metal/organic heterostructures, have been fabricated. Attractive features of these materials offer the possibility for device processing, compatibility with flexible substrates, and low materials consumption for ultra thin molecular films, all of which give the prospect of cheaper photovoltaic energy generation [16].…”
Section: Introductionmentioning
confidence: 99%